2017
DOI: 10.1002/aqc.2803
|View full text |Cite
|
Sign up to set email alerts
|

Testing the exclusion capabilities and durability of the Sharksafe Barrier to determine its viability as an eco‐friendly alternative to current shark culling methodologies

Abstract: 1. Following a shark attack, local governments often rapidly respond by implementing indiscriminate shark culls. These culls have been demonstrated to have substantial localized and adverse effects on a variety of marine organisms, and therefore there is an increasing need for an ecofriendly alternative that maximizes both beachgoer and marine organismal safety.2. In response to such culls, the novel magnetic barrier technology, the Sharksafe Barrier was developed and rigorously tested on a variety of sharks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 25 publications
2
22
5
Order By: Relevance
“…The voltages caused by the induction-based mechanism of the magnets substantially exceed the detection threshold of elasmobranchs (e.g., Jordan, Mandelman & Kajiura, 2011 ; Kajiura & Fitzgerald, 2009 ). Permanent magnets have also been shown to elicit avoidance in a range of species, including Galapagos ( C. galapagensis ), hammerhead ( S. mokarran and S. lewini ), lemon ( Negaprion brevirostris ), Australian blacktip ( Carcharhinus tilstoni ), grey reef ( C. amblyrhynchos ), bull ( C. leucas ), milk ( Rhizoprionodon acutus ), speartooth ( Glyphis glyphis ), and white sharks ( O’Connell et al, 2018 ; O’Connell et al, 2014a ; O’Connell et al, 2014b ; O’Connell et al, 2015 ; O’Connell et al, 2011 ; O’Connell et al, 2010 ; Rigg et al, 2009 ; Robbins, Peddemors & Kennelly, 2011 ). However, the distance from which sharks reacted to magnets in those studies was small, typically <0.5 m ( O’Connell et al, 2014a ; Rigg et al, 2009 ) and the effectiveness of the magnets decreased with increasing shark motivation ( Robbins, Peddemors & Kennelly, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The voltages caused by the induction-based mechanism of the magnets substantially exceed the detection threshold of elasmobranchs (e.g., Jordan, Mandelman & Kajiura, 2011 ; Kajiura & Fitzgerald, 2009 ). Permanent magnets have also been shown to elicit avoidance in a range of species, including Galapagos ( C. galapagensis ), hammerhead ( S. mokarran and S. lewini ), lemon ( Negaprion brevirostris ), Australian blacktip ( Carcharhinus tilstoni ), grey reef ( C. amblyrhynchos ), bull ( C. leucas ), milk ( Rhizoprionodon acutus ), speartooth ( Glyphis glyphis ), and white sharks ( O’Connell et al, 2018 ; O’Connell et al, 2014a ; O’Connell et al, 2014b ; O’Connell et al, 2015 ; O’Connell et al, 2011 ; O’Connell et al, 2010 ; Rigg et al, 2009 ; Robbins, Peddemors & Kennelly, 2011 ). However, the distance from which sharks reacted to magnets in those studies was small, typically <0.5 m ( O’Connell et al, 2014a ; Rigg et al, 2009 ) and the effectiveness of the magnets decreased with increasing shark motivation ( Robbins, Peddemors & Kennelly, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter would add weight to the board and diminish its performance. However, several studies have shown the potential use of strong magnets in combination with visual deterrents to prevent sharks from entering some areas (e.g., beaches, embayments) ( O’Connell et al, 2018 ; O’Connell et al, 2014b ). Neodymium-iron-born (‘rare earth’) magnet is the strongest permanent magnet currently available and could be a more powerful deterrent than ferrite magnets.…”
Section: Discussionmentioning
confidence: 99%
“…Other bather protection measures include: (1) physical barriers that aim to provide an impassable obstacle that separates sharks from people; (2) visual barriers, such as bubble curtains, that are not physically impassable but present aversive visual stimuli; and (3) barriers that aim to exploit sharks' aversion to particular electrical and electromagnetic stimuli (O'Connell et al 2014a(O'Connell et al , 2014b(O'Connell et al , 2014cMcPhee and Blount 2015). Combined deterrents are also under investigation, such as the SharkSafe Barrier (Sharksafe Barrier TM , Stellenbosch, South Africa; https://www.sharksafesolution.com/, accessed November 2019), which combines an electromagnetic deterrent with PVC piping that mimics dense kelp beds, creating a threshold that large sharks may be unwilling to cross (McPhee and Blount 2015;O'Connell et al 2018). Personal deterrents, designed to be worn or carried by an individual swimmer or surfer, are not considered in detail here, but are reviewed by O'Connell et al (2014c) and Hart and Collin (2015).…”
Section: Introductionmentioning
confidence: 99%
“…The quick succession of shark bites occurring in multiple locations has led to the development and use of various shark bite mitigation measures (e.g., personal deterrents; surveillance/realtime monitoring), many of which still need to be assessed. Although a few devices have recently been tested (e.g., Huveneers et al, 2013bHuveneers et al, , 2018bKempster et al, 2016;O'Connell et al, 2018), there is a need for transparency and standardization of protocols and variables used to test the effectiveness of personal and arearelated deterrents. Ensuring such consistency will enable direct comparisons of products and mitigation measures.…”
Section: Can We Reliably Assess and Significantly Reduce Human-shark mentioning
confidence: 99%
“…This could potentially result in public pressure to downgrade or remove legislated protection or to initiate targeted culls (Ferretti et al, 2015). The emotional response of the public to human-shark interactions (Crossley et al, 2014) and negative media portrayal (Muter et al, 2013;Sabatier and Huveneers, 2018) requires scientists and managers to rethink how to reconcile public safety in a proactive manner with the recovery of populations and increase the capacity for education to change public perception (Pepin-Neff and Wynter, 2018).…”
Section: Can We Reliably Assess and Significantly Reduce Human-shark mentioning
confidence: 99%